Discrepancies on Medication Plans detected in German Community Pharmacies. Issue 5 (2nd July 2015) - Waltering, Isabel; Schwalbe, Oliver; Hempel, Georg
Abstract Rationale, aims and objectives A current medication plan was identified as important patient safety factor. Information is needed on how many patients possess such a plan and what problems can be identified with its use. This study tried to define factors that influence accuracy of medication plans and to detect discrepancies from planned and actually administered medication in polypharmacy patients. Methods Participants of the 'Apo‐AMTS' course in Germany evaluated medication plans from their patients during performing medication reviews in community pharmacies. Discrepancies were defined as additional or missing drugs and deviations in dosage and drug names for Rx drugs and missing or additional self‐medication. Results Eighty per cent of the patients possessed a medication plan mainly written by general practitioners. Only 6.5% of the plans showed no discrepancies. Most discrepancies were seen on medication plans written by medical specialists and general practitioners, mainly name aberrations (41%) followed by additional drugs taken (30%) and prescribed drugs no longer taken (18%). Dosage variance was seen in 11% of all discrepancies. Deviations from the plan were observed frequently with antihypertensives (31.4%), analgesics (11.3%) and antidepressants/hypnotics as well as lipid‐lowering drugs (6.7%). Four hundred thirty‐three OTC drugs were not listed, mainly analgesics, mineral supplements and laxatives. Conclusion Many patients possess a medication plan but most of these plans showed discrepancies which limits the use as patient safety indicator. Community pharmacies offering medication reviews have an essential position to use the medication plan as a central link between patients and their prescribers, and therefore improve patient safety.